Stress-strain behavior of high-strength concrete confined by ultra-high- and normal-strength transverse reinforcements - Li, Bing. (2012)
When high-strength concrete is used for reinforced concrete members subjected to seismic loading, it is more difficult to achieve ductile behavior of such members than when normal-strength concrete is used. In this paper, an experimental study of a number of quasi-static axial loading tests on high-strength concrete specimens confined by various amounts of transverse reinforcement is described. The main parameters were concrete strengths ranging from 35.2 to 82.5 MPa and yield strength of Grade 430 and 1300 transverse reinforcement. A stress-strain relationship for confined high-strength concrete is proposed that is found to give reasonably good prediction of the experimental behavior of circular and square specimens with high-strength concrete confined by either normal- or ultra-high-yield-strength with various configurations. An empirical formula for the ultimate longitudinal strain of confinedhigh-strength concrete corresponding to the first hoop or spiral fracture is also proposed.